SURVEI TINGKAT KEMAMPUAN SERVIS BAWAH DAN SERVIS ATAS PERMAINAN BOLA VOLI SISWA KELAS VIII SMP TENERA AGRICINAL BENGKULU UTARA - Setyawan, Debby -; Mesterjon, Mesterjon; Banat, Azizatul (Educative Sportive, 2022)
AbstractThis research is a qualitative research with a survey method in which the subjects in this study are class VIII SMP Tenera Agricinal Bengkulu Utara, totaling 20 students. The data collection techniques in this study were observation, service tests, and documentation to determine the level of ability to serve and serve in volleyball at the Tenera Agricinal Junior High School Bengkulu Utara. It is known that the results of the lower service test are categorized as very good at 20%, good at 25%, sufficient by 40%, less by 10%, and very less by 5%, while the results of the upper service test are categorized as very good at 20%. good by 25%, sufficient by 40%, less by 10%, and very less by 5%. So it can be concluded that from the lower service test and the upper service test, there are the same results, which are sufficient. Keyword: Ability level survey, bottom service, top service